Discretized collision operator for simulations of fusion non-maxwellian plasma relaxation - Shyshkin, O.A.; Vozniuk, D.V.; Girka, I.O. (Вопросы атомной науки и техники, 2018)
The plasma observed in modern fusion devices very often exhibits strongly non-Maxwellian distribution. This is the result of magnetic field lines reconnection with formation of magnetic resonant structures like magnetic islands and stochastic layers. Along with that, the plasma heating by means of neutral beam injection (NBI) and ion/electron cyclotron resonance frequency (ICRF/ECRF) heating induce the non-Maxwellian fast ions. In order to get the comprehensive description of plasmas one should take care of plasma particles interaction, i.e. Coulomb collisions in non-Maxwellian environment. In present paper the expression for the discretized collision operator of a general Monte Carlo equivalent form in terms of expectation values and standard deviation for the non-Maxwellian bulk distribution function is derived for a magnetized plasma assuming distribution function isotropy. The simulation for relaxation of fusion product fractions like -particles, protons and deuterium ions on background plasma particles is performed with the use of presented collision operator. On this purpose the δ-function distribution for the bulk plasmas is assumed.